2022
DOI: 10.1186/s13148-022-01389-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel blood-based FUT7 DNA methylation is associated with lung cancer: especially for lung squamous cell carcinoma

Abstract: Background The death rate of lung cancer (LC) ranks first in the world. Changes of DNA methylation in peripheral blood may be related to malignant tumors. It is necessary to explore blood-based biomarkers of methylation to detect LC. Methods Mass spectrometry assays were conducted to measure DNA methylation levels of seven CpG sites within FUT7 gene in the peripheral blood of 428 patients with LC, 233 patients with benign pulmonary nodule (BPN) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This study analyzed the relationship between CTLA-4 and FAM20A and found a positive correlation in their expression in LUSC. CTLA-4 interacts with CD80, thereby limiting T-cell activation and leading to immune dysfunction (41). Interestingly, the level of CD80 and FAM20A was also favorably correlated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This study analyzed the relationship between CTLA-4 and FAM20A and found a positive correlation in their expression in LUSC. CTLA-4 interacts with CD80, thereby limiting T-cell activation and leading to immune dysfunction (41). Interestingly, the level of CD80 and FAM20A was also favorably correlated.…”
Section: Discussionmentioning
confidence: 97%
“…Methylation of CpG sites in the promoter region is believed to influence the process of DNA transcription by silencing the transcription factors ( 43 ), and without altering the DNA sequence. The methylation of AKAP13, nuclear receptor binding SET domain protein 3 (NSD3), and FUT7 are connected with the diagnosis of LUSC patients ( 44 , 45 ). Our study indicated that hypermethylation of cg24064639 is associated with poorer prognosis, suggesting that epigenetic changes might impact LUSC progression by inhibiting FAM20A transcription.…”
Section: Discussionmentioning
confidence: 99%
“…FUT4 and FUT7 may also participate in lung-to-brain metastasis of NSCLC cells ( 117 ). Reduced levels of FUT7 CpG DNA methylation have been found in lung cancer, especially in LUSC ( 118 ), and FUT7 promotes lung cancer proliferation by activation of the EGFR/AKT/mTOR signal pathway ( 119 ). FUT8, whose expression is upregulated in most cancers, regulates the core fucosylation of PD-1 ( 120 , 121 ), PD-L2 ( 122 ), TGF-β ( 123 ), TNFR ( 124 ), EGFR ( 78 , 125 , 126 ), B7H3 ( 127 ), α3β1 integrin ( 128 ), and E-cadherin ( 129 ) as well as that of mucins ( 130 ).…”
Section: Glycoenzyme-based Protein Glycosylation Changes In Crdsmentioning
confidence: 99%
“…This study analyzed the relationship between CTLA-4 and FAM20A and found a positive correlation in their expression in LUSC. CTLA-4 interacts with CD80, thereby limiting T-cell activation and leading to immune dysfunction (41). Interestingly, the level of CD80 and FAM20A was also favorably correlated.…”
Section: Discussionmentioning
confidence: 97%